2021
DOI: 10.1021/acs.inorgchem.0c03661
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Synthesis of a Uranyl Peroxo Complex Facilitated by Hydrothermally In Situ Formed Organic Peroxide

Abstract: Because H2O2 is thermally unstable, it seems to be difficult to synthesize peroxides at elevated temperatures. We describe here the in situ generation of peroxide that is incorporated in a new uranyl peroxo complex, HT-UPO1, through the hydrothermal treatment of uranyl nitrate at 150 °C in the presence of organic ligands. In this novel process, a highly conjugated aromatic carboxylate linker, (E)-4-[2-(pyridin-4-yl)­vinyl]­benzoic acid (HPyVB), plays a crucial role by inducing the reduction of oxygen in air to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Furthermore, some UO 2 2+ complexes have been reported to react with O 2 or H 2 O 2 to form uranyl-peroxo complexes. 40 However, such a uranyl-peroxo complex was not observed in the aerobic oxidation of 1 to 2 . This is due to the fact that both axial and equatorial coordination sites of these UO 2 2+ complexes are fully saturated, and thus O 2 has little chance to directly access UO 2 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some UO 2 2+ complexes have been reported to react with O 2 or H 2 O 2 to form uranyl-peroxo complexes. 40 However, such a uranyl-peroxo complex was not observed in the aerobic oxidation of 1 to 2 . This is due to the fact that both axial and equatorial coordination sites of these UO 2 2+ complexes are fully saturated, and thus O 2 has little chance to directly access UO 2 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The O-O distance of peroxo group is 1.537(9) Å, which is consistent with those reported in other uranyl peroxide compounds and rule out the possibility of misidentification of hydroxyl groups. 44,45 Although photoinduced reduction of oxygen in air in the presence of uranyl ion to generate peroxide has been previously reported in several studies, [46][47][48][49] what is found here should be a type of thermally-induced oxygen reduction, 50 where the reductive capability of organic ligand C[4]R towards oxygen atmosphere at elevated temperatures and its coordination stabilization effect on dimeric uranyl units bridged by in-situ formed peroxide groups (Figure 2a) is crucial to final formation of UOC. In addition to (μ2-η 2 , η 2 )-coordinated peroxo group, each eight-fold coordinated uranyl is also coordinated to another two η 2 -carboxyl groups (Figure 2b) with slightly longer U-O(carboxyl) bonds (2.404(7) Å-2.539(7) Å) than those of U-O(peroxo) bonds (2.317(6) Å-2.370(6) Å) (Table S2), thus taking a hexagonal bipyramid geometry.…”
Section: Synthesis and Characterization Of Uocmentioning
confidence: 48%
“…The O-O distance of peroxo group is 1.537(9) Å, which is consistent with those reported in other uranyl peroxide compounds and rule out the possibility of misidentification of hydroxyl groups. 44,45 Although photoinduced reduction of oxygen in air in the presence of uranyl ion to generate peroxide has been previously reported in several studies, [46][47][48][49] what is found here should be a type of thermally-induced oxygen reduction, 50 where the reductive capability of organic ligand C[4]R towards oxygen atmosphere at elevated temperatures and its coordination stabilization effect on dimeric uranyl units bridged by in-situ formed peroxide groups (Figure 2a) is crucial to final formation of UOC. In addition to (μ2-η 2 , η 2 )-coordinated peroxo group, each eight-fold coordinated uranyl is also coordinated to another two η 2 -carboxyl groups (Figure 2b) with slightly longer U-O(carboxyl) bonds (2.404(7) Å-2.539(7) Å) than those of U-O(peroxo) bonds (2.317(6) Å-2.370(6) Å) (Table S2), thus taking a hexagonal bipyramid geometry.…”
Section: Synthesis and Characterization Of Uocmentioning
confidence: 48%